Estimation of Catha edulis (Vahl) Forssk. ex Endl. - antidiabetic drug interactions by using closed-loop Doluisio's method - Ahmed M. Al-Ghani; Mohammed A. Al-Khawlani; Anes A.M. Thabet (GarVal Editorial Ltda., 2023)
Context: Catha edulis (khat) is a prevalent plant in Yemen and other African regions. In Yemen and other countries, most people chew this plant, which may change the pharmacokinetics of many drugs, such as anti-diabetics (glibenclamide and metformin). Aims: To evaluate the effect of C. edulis presence in the gastrointestinal tract (GIT) on the intestinal perfusion and bioavailability of metformin and glibenclamide and its effectiveness. Methods: The present study was conducted in situ using the closed-loop Doluisio's method. Rat intestinal perfusion of a reference standard of each test drug alone was compared to the drug intestinal perfusion in the presence of C. edulis (three types of C. edulis agriculture in different regions of Yemen). The type of C. edulis that produced the most influence on the absorption of the drug reference was then re-investigated using the same in situ method against a pharmaceutical dosage form (tablets) of the drug. Results: The intestinal absorptions (perfusion) of reference standards of metformin and glibenclamide were decreased in the presence of C. edulis by 30.53-35.9% and 14.71-27.93%, respectively, while such decrease with pharmaceutical dosage form (tablets) of the two drugs was 24.24 and 19.77%, respectively. Conclusions: Based on the results reached from this study, the anti-diabetic bioavailability was significantly reduced in the presence of C. edulis, and this effect may affect the drug efficacy.